Understanding Poetry in Teaching English as a Foreign Language in Indonesia - *, Arjulayana; Srikandi, Cut Novita (Sebelas Maret University, 2016)
This paper aimed to report the data analysis of teaching English as a foreign language in 7th semester students of Muhammadiyah University Tangerang. This paper can be given understanding about how does a Poetry can be used as a media in teaching English for students in University. The data analysis in this paper use qualitative descriptive, because this technique embedded the students understanding of poetry and EFL gather. Through this paper can be known that teaching EFL can implement through Understanding Poem, where the poem is consist of complex words which has intensely meaning than does ordinary language. This paper will report the data how a poem can use as a unique media and able to give understanding in teaching Indonesian students university.